DETERMINING GREEN MARKETING PRACTICES AND SATISFACTION OF MEMBERS OF MARKETING COOPERATIVE SOCIETIES IN AWKA SOUTH LOCAL GOVERNMENT AREA, ANAMBRA STATE, NIGERIA (Journal of Global Accounting, 2025)
The study investigated the relationship between green marketing practices and satisfaction of members of marketing cooperative societies in Awka South Local Government Area. Two research questions and two hypotheses tested at 0.05 level of significance guided the study. The survey design was adopted for the study and the population of the study was 100 members of marketing cooperative societies in Awka South LGA of Anambra State, Nigeria. Two validated instruments were used to collect data for the study. Pearson Product Moment Correlation was used to analyze the research questions and test the hypotheses in the study. The findings of the study revealed that eco-labeling and eco-branding practices have high positive relationship with satisfaction of members of marketing cooperative societies in Awka South Local Government Area. Based on the findings of the study, the researcher recommended that heads of cooperative societies should emphasise the use of eco-labels on products to inform members about the environmental benefits of their purchases. Furthermore, the researchers recommended that cooperative societies should develop strong eco-branding strategies that would show the cooperative’s commitment to sustainability.
Keywords: Cooperative Societies; Eco-branding, Eco-labeling; Green Marketing; Satisfaction